Travelling Wave Solutions of Nonlinear Dynamical Equations in a Double-Chain Model of DNA - Zheng-yong Ouyang; Shan Zheng (Abstract and Applied Analysis)
We consider the nonlinear dynamics in a double-chain model of DNA which consists of two long elastic homogeneous strands connected with each other by an elastic membrane. By using the method of dynamical systems, the bounded traveling wave solutions such as bell-shaped solitary waves and periodic waves for the coupled nonlinear dynamical equations of DNA model are obtained and simulated numerically. For the same wave speed, bell-shaped solitary waves of different heights are found to coexist.